Superior mesenteric artery injury during laparoscopic radical nephrectomy - E. A. Kruglov; A. I. Narkevich; A. I. Babich; Y. A. Pobedintseva; V. A. Kudlachev; E. V. Filimonov; A. N. Goncharov; V. M. Unguryan (Исследования и практика в медицине, 2018)
The authors present to your a en on a rare clinical case of complete intersec on of the superior mesenteric artery in laparoscopic radical nephrectomy. This complica on emerged in the process of learning the technique of laparoscopic radical nephrectomy, before reaching the “plateau” of the learning curve, in condi ons of poor vision and in the interposi on of tissues due to paratumorous inﬁtiltra on. This type of injury has a high risk of total necrosis of the small intestine. However, due to the concerted ac ons of the surgical service and the readiness of surgeons to complete the vascular suture of the main vessels, a successful reimplanta on of the superior mesenteric artery into the aorta was performed. This is conﬁ rmed by postopera ve observa on and examina on, which included CT angiography. It should be noted that descrip ons of cases of aor c reimplanta on of the superior mesenteric artery are extremely rare in the world and national literature, except for cases of mesenteric ischemia. This case contributes to the description of rare cases of aor c reimplanta on of the superior mesenteric artery and shows the correctness of the selected surgical tactics.